True colors - Kinsey-Warnock, Natalie (Alfred A. Knopf, 2012)
In 1952 Vermont, ten-year-old Blue decides to set out in the middle of her town's sesquicentennial celebration to find the mother who abandoned her as a baby, but a series of events reminds her that she already has everything she needs.